Profil Kemampuan Multi Representasi dalam Menyelesaikan Soal Cerita pada Siswa dengan Gaya Belajar Auditori - Danisa Putri Indriyani; Nizaruddin Nizaruddin; Dewi Wulandari (Jurnal Kualita Pendidikan, 2021)
The importance of multiple mathematical representations for students in learning is that one of them can help students learn and build a concept to overcome a problem in solving story problems. The purpose of this study was to determine the profile of multi-representation abilities in solving story problems for students with auditory learning styles. This type of research is descriptive qualitative research. The subjects in this study were four students with auditory learning styles from class XI IPA 1 SMA Negeri 1 Bangsri. Data collection methods used are learning style questionnaire tests, mathematical representation tests, and interviews. The results of this study indicate that students with auditory learning styles based on mathematical representation abilities are able to solve all the questions given. In solving story problems, the subject always writes down what is known and asked first, then answers the problem. Subjects use visual representations in the form of illustrations and tables to make it easier to answer. Next, the subject writes down what is known and asked using verbal and symbolic representations according to what is written on the problem. Auditory subjects solve these problems by involving symbolic representations (mathematical expressions) by substituting them into mathematical formulas. To explain the important part of the problem and write a conclusion at the end of the subject's answer, use a verbal representation in the form of words, sentences, or written text.